A literary-historical analysis of Daniel 2: two powers in opposition - M. Nel (Acta Theologica)
This article investigates some aspects of Daniel 2 and attempts to demonstrate the value of the literary-historical approach to biblical texts. The literary-historical approach consists of three   elements: a structural, a historical and a narrative analysis of the text. Firstly, the structural investigation uses Propp’s model for a functional analysis of the text, followed by a semiotic analysis to identify the functions and qualifications in the text. A description of the functions and qualifications is essential in order to identify the text’s pertinent transformations as well as its underlying semiotic squares. The latter enables the researcher to formulate the theological values or persuasions which the writer wished to convey to her readers. Secondly, synchronic and diachronic insights are integrated in an analysis of the text. Lastly, the results of the study are concluded in a narrative synthesis, in terms of the narrator, setting, characters, plot and style. In Daniel 2 the Babylonian king, shortly after being enthroned, dreams about his political insecurity. The narrator emphasises that it is God who appoints and dethrones kings. He reveals the future (Dan. 2:29, 47). He rules over the world (Dan. 2:21, 37, 44), and He cares for His people (Dan. 2:48-49). Israel will rule over the world once God destroys all other kingdoms (Dan. 2:44-45). The narrator of Daniel 2 conveys two persuasions to her readers: she emphasises the sovereign rule of God, not only in Jerusalem but also in Babylon, and the responsibility of the faithful. Most researchers accept that the tale in Daniel 2 is not literally true. It should be read as a literary text. However, the tale has also functioned in various historical contexts and should be read from a historical-critical perspective. The hypothesis of this article is that the tale in Daniel 2 would be better understood if read from a literary as well as historical perspective.